2003
DOI: 10.1016/s0006-3495(03)70010-1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Protein Conformational Flexibility on the Electronic Properties of a Chromophore

Abstract: In this paper we address the question of how a protein environment can modulate the absorption spectrum of a chromophore during a molecular dynamics simulation. The effect of the protein is modeled as an external field acting on the unperturbed eigenstates of the chromophore. Using a first-principles method recently developed in our group, we calculated the perturbed electronic energies for each frame and the corresponding wavelength absorption during the simulation. We apply this method to a nanosencond times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 55 publications
2
32
0
Order By: Relevance
“…Recent literature (18)(19)(20) has shown that, under native conditions, biomacromolecules should be considered as an ensemble of conformational states rather than as a single static picture, being subject to thermal fluctuations and conformational transitions which might play a key-role in fine tuning the biological activity. Similar conclusion was drawn in our previous paper (15), where it was found that after an exothermic and mechanically hindered proton transfer (from H 2 O 2 to His42), the reaction pocket at room temperature is in equilibrium between two conformations, differing essentially for the His42 position, and Cpd0 formation is therefore characterized by a large entropic contribution.…”
Section: Introductionmentioning
confidence: 99%
“…Recent literature (18)(19)(20) has shown that, under native conditions, biomacromolecules should be considered as an ensemble of conformational states rather than as a single static picture, being subject to thermal fluctuations and conformational transitions which might play a key-role in fine tuning the biological activity. Similar conclusion was drawn in our previous paper (15), where it was found that after an exothermic and mechanically hindered proton transfer (from H 2 O 2 to His42), the reaction pocket at room temperature is in equilibrium between two conformations, differing essentially for the His42 position, and Cpd0 formation is therefore characterized by a large entropic contribution.…”
Section: Introductionmentioning
confidence: 99%
“…This clearly limits the theoretical investigation to rather static information excluding the coupling between electronic properties and molecular motions, which can be essential for spectroscopic properties and chemical reactions. In this Letter, we perform a computational study of formaldehyde in water, using the recently introduced perturbed matrix method (PMM) [5,6] to obtain formaldehyde vertical excitation energy from molecular dynamics (MD) simulation data. This simple molecule has been extensively studied with a variety of quantum chemical procedures [7][8][9][10] and hence it is very suited for evaluating PMM accuracy, compared to other approaches.…”
Section: Introductionmentioning
confidence: 99%
“…The application of PMM provides rather good results for reproducing complicated observables such as the absorbtion spectrum of a highly fluctuating molecule in solution. However, unlike the heme in protein environment, [16,17] the relative ground-excited states electronic properties of MMP-5 in aqueous solution are not modulated by the conformational fluctuations of the molecular environment. This observation plausibly indicates some intrinsic differences emerging when this species is within its natural environment and when it is in aqueous solution.…”
Section: Uv/vis Spectrum Of Aqueous Mmp-5mentioning
confidence: 99%
“…[16,17] In fact when we were dealing with an enzyme, the solvent field had only a limited and indirect role concerning the perturbation of the transitions. More precisely, the solvent was normally found to play the role of modulating the fluctuation of the protein whose field is, on the other hand, mainly responsible for the perturbation.…”
Section: Uv/vis Spectrum Of Aqueous Mmp-5mentioning
confidence: 99%
See 1 more Smart Citation